Semiparametric diffusion estimation and application to a stock market index - Wolfgang Härdle; Torsten Kleinow; Alexander P. Korostelev; Camille Logeay; Eckhard Platen (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
The analysis of diffusion processes in financial models is crucially dependent on the form of the drift and diffusion coefficient functions. A methodology is proposed for estimating and testing coefficient functions for ergodic diffusions that are not directly observable. It is based on semiparametric and nonparametric estimates. The testing is performed via the wild bootstrap resampling technique. The method is illustrated on S&P 500 index data.
urn:nbn:de:kobv:11-10049482
Keywords: C51; C52; G22; 330; Identification; Bootstrap; Diffusion; Continuous-time financial models; Semiparametric methods; Kernel smoothing